The Role of Students' Developmental Psychology in Mathematics Learning - Nurwahid, Mohammad; Hidayatullah, Bagus; Atho’ul Malik, Fatus; Amalliyah, Nor; Setiawan, Wahyu (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Mathematics learning requires an approach that is appropriate to students' developmental stages to ensure optimal understanding. Developmental psychology plays a role in understanding the cognitive, emotional and social characteristics of students, so that learning can be tailored to their needs. This study uses a literature analysis method by examining various theories and research on developmental psychology and their implications for mathematics learning. The results of the study show that developmental psychology helps teachers adapt learning strategies to students' cognitive stages, overcome mathematics anxiety, and encourage social collaboration to increase learning motivation